Assessing Technological Pedagogical Content Knowledge Proficiency Among Prospective Mathematics Teachers in Micro-Learning Courses - Nuraeni, Reni; Juandi, Dadang (Department of Mathematics Education Program IPI Garut, 2023)
Calon guru wajib memiliki, menguasai, dan meningkatkan Pengetahuan Konten Pedagogis Teknologi (TPACK), yang diakui sebagai elemen penting dalam dekonstruksi pengetahuan guru. Penelitian ini berupaya menganalisis kemahiran TPACK siswa calon guru yang mengikuti mata kuliah Micro-Learning. Dengan menggunakan pendekatan penelitian deskriptif kualitatif, pengumpulan data dilakukan melalui lembar observasi dan wawancara. Analisis data meliputi reduksi, penyajian, dan penarikan kesimpulan. Temuan menunjukkan bahwa ketiga peserta menunjukkan kemampuan TPACK yang patut dipuji, meskipun masih terdapat ruang untuk mengoptimalkan Pengetahuan Teknologi dalam konteks pembelajaran. Prospective teachers are required to possess, master, and enhance their Technological Pedagogical Content Knowledge (TPACK), which is recognized as a pivotal element in the deconstruction of teacher knowledge. This study seeks to analyze the TPACK proficiency of prospective teacher students enrolled in a Micro-Learning course. Employing a descriptive qualitative research approach, data was collected through observation sheets and interviews. Data analysis encompassed reduction, presentation, and conclusion-drawing. The findings revealed that the three participants exhibited commendable TPACK abilities, although there is room for optimizing Technological Knowledge in the context of learning.